A SUCCESSFULLY TREATED CASE OF HYPEROSMOLAR HYPERGLYCEMIC STATE WITH RHABDOMYOLYSIS IN AN OBESE YOUNG MAN - Kim, Kyujin (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Rhabdomyolysis is a syndrome caused by muscle breakdown which releases intracellular contents into the bloodstream. Rhabdomyolysis can be a life-threatening condition causing acute kidney injury and hyperosmolar hyperglycemic state in a diabetic patient. CASE A 30-year-old Korean male presented to the emergency department with bilateral lower extremity weakness and mental status changes. He had been recently experiencing fatigue, polyuria and polydipsia, as well as 6 kg weight loss over the past 3 days (120 kg, BMI 40.6). He was admitted to our intensive care unit due to impression of hyperosmolar hyperglycemic state combined with acute kidney injury. CONCLUSION Obese men with uncontrolled diabetes mellitus can be prone to rhabdomyolysis combined with a hyperosmolar hyperglycemic state. Delayed detection can be fatal, and timely renal replacement therapy can result in an excellent prognosis. Therefore, it is crucial for clinicians to detect and treat such patients as soon as possible to avoid impairing their renal function.